Historiozoficzny apokaliptyzm C. G. Junga - Bytniewski, Bytniewski (Hybris, 2016)
Critique of culture is one of the biggest parts of philosophy/psychology created by Carl Gustav Jung. Jung was witness of World War I and World War II, his thought was deeply influenced by writings of F. Nietzsche, who assured us that we (modern people) are sentenced to Age of nihilism. Jung seemed to take over this belief, developing it inside his own philosophical system. In Jung’s way of thinking Age of nihilism turned into a monumental discourse about New Age, where overgrown Enlightment’ Reason must abdicate, leaving its position to The Age of new spirituality. In my paper I’m trying to present thought of The Swiss psychologist as an apocalyptical prophecy, but not only apocalyptical. My aim is to find bright beam among this very pessimistic part of his oeuvre.